Long-term Outcomes (5 Years or More) After Myotomy. Issue 4 (December 2022) - Capovilla, Giovanni; Costantini, Andrea; Provenzano, Luca; Costantini, Mario; Salvador, Renato
Background: Surgical or endoscopic myotomy are good options for treating achalasia, as >80% of patients continue to report no symptoms at medium-term follow-up. Little is known about the long-term natural history of patients who have undergone myotomy, however, in terms of symptom control, need for retreatment, and complications. In this review we examined the long-term results at least 5 years after surgical or endoscopic myotomy. Methods: A narrative review of all studies reporting the results of surgical or endoscopic myotomy with a follow-up of 5 years or more was conducted. The main focus was on symptom relief, the incidence of GERD, and the need for retreatment. Results: Transthoracic or laparotomic approaches to Heller myotomy were mainly used in the last century, with long-term studies reporting symptom relief in the range of 73% to 95%, and a 4.4% to 45.5% incidence of GERD. The laparoscopic approach has been the gold standard for the last 20 years, eliminating dysphagia symptoms in 65% to 95% of patients. Per-oral endoscopic myotomy (POEM) is a valid method that achieves long-term symptom relief in up to 92% of patients. GERD remains an issue as it's incidence after POEM exceeds that reported after laparoscopic myotomy. Conclusion: Surgical and endoscopic myotomy both achieve symptom control that persists for more than 5 years and can be accepted as an effective primary treatment for achalasia. However, the real role of the higher incidence of postoperative reflux carried by POEM should not be underestimated.